2008
DOI: 10.1016/j.renene.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the cathode flooding on the transient responses of a PEM fuel cell

Abstract: This study investigates the effects of the flooding of the gas diffusion layer (GDL), as a result of liquid water accumulation, on the performance of a proton exchange membrane fuel cell (PEMFC). The transient profiles of the current generated by the cell are obtained using the numerical resolution of the transport equation for the oxygen molar concentration in the unsteady state. The dynamics of the system are captured through the reduction of the effective porosity of the GDL by the liquid water which accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The results show that CCL behaves similar to watershed in the fuel cell which helps to balance the opposite water flux across the membrane and cathode region outlet. Najjari et al [78] conducted experiments to observe the effects of water flooding on GDL because of the accumulation of water in the fuel cell and their results confirmed that excess liquid water affects fuel cell performance drastically. Najjari et al [78] concluded that a thinner GDL will result in a lower resistance for oxygen transport and liquid water is more likely to block the pores easily than vice-versa.…”
Section: Impact At the Cathodementioning
confidence: 93%
“…The results show that CCL behaves similar to watershed in the fuel cell which helps to balance the opposite water flux across the membrane and cathode region outlet. Najjari et al [78] conducted experiments to observe the effects of water flooding on GDL because of the accumulation of water in the fuel cell and their results confirmed that excess liquid water affects fuel cell performance drastically. Najjari et al [78] concluded that a thinner GDL will result in a lower resistance for oxygen transport and liquid water is more likely to block the pores easily than vice-versa.…”
Section: Impact At the Cathodementioning
confidence: 93%
“…PEMFC is a complex multi-physics system which can be described at different scales and can be established for different purposes: to design specific materials or devices [24], to conceive the stack control algorithm [25][26][27] or to assess the performances of the whole system (FC plants, HEV) [28]. The main objective of this section is to emphasize the key parameters of each subsystem in the global output voltage expression and more precisely on the hysteresis phenomena.…”
Section: Pem Fuel Cell Modelmentioning
confidence: 99%
“…Mass transfer also played an important role on current overshoot behavior during start-up due to the formation of liquid water, which can reduce the effective porosity of gas diffusion layer. Najjari et al [19] developed a two-dimensional transient model for the cathode gas diffusion layer to examine the effects of correlative parameters of gas diffusion layer on transient behavior of average current density. With the increase of porosity, thickness and convective mass transfer coefficient of gas diffusion layer, the magnitude of current overshoot increased, and the maximum value of current overshoot decreased with the increase of shoulder width, indicating that both the oxygen transfer resistance and flooding played important roles in transient behavior of average current densities.…”
Section: Introductionmentioning
confidence: 99%